Emotional Intelligence and Personal Development in Employees: A Case Study of Zigron Corporation, Pakistan - Akram, Tayyaba; Haider, Muhammad Jamal; Akram, Muhammad Waqar (Bina Nusantara University, 2016)
Article sought to explore the potential role of Emotional Intelligence (EI) in the personal development of organizational employees and to find out the scope of emotional intelligence for personal development of individuals. This study was qualitative in nature; however, to ensure the authenticity and generalizability of the results some quantitative analysis analyses were applied. Using case study method and taking interviews from 17 software house engineers of Zigron Corporation in Pakistan, this study suggests that emotional intelligence plays a crucial role in the personal development of individuals.